Sosialisasi Pencegahan Tindak Pidana Korupsi dengan Menggunakan Metode Pembelajaran Berbasis Masalah pada TK Al-Kawanad - Zainuddin; Ramli; Syarifuddin Hasyim; Ajinar; Wolly Mistiar; Adi Saleh; Afriani; A’zizah (Yayasan Kawanad, 2023)
Corruption has become a serious problem in Indonesia and the prevention of corruption needs to be done from an early age. One effort that can be taken is to conduct socialization on corruption prevention through problem-based learning methods at TK Al-Kawanad. This method can help children understand the dangers of corruption and how to prevent it through direct experience in solving corruption problems. This study aims to analyze the effectiveness of problem-based learning methods in socializing corruption prevention at TK Al-Kawanad. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The results show that problem-based learning methods are effective in improving children's understanding of the importance of corruption prevention and how to prevent it. In addition, children are also more motivated and involved in learning through this method. This study is expected to provide a positive contribution in efforts to prevent corruption in Indonesia through character education from an early age.